2017
DOI: 10.1590/1981-6723.7216
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and antioxidant activity of two bean cultivars (Phaseolus vulgaris L.) submitted to cooking

Abstract: Phenolic compounds and antioxidant activity of two bean cultivars (Phaseolus vulgaris L.) submitted to cooking Compostos fenólicos e atividade antioxidante de duas cultivares de feijões (Phaseolus vulgaris L.) submetidos à cocção AbstractThe common bean (Phaseolus vulgaris L.) is a source of nutrients and contains phenolic compounds that act as antioxidants. The aim of the present study was to determine the phenolic compounds and tannins in two bean cultivars (Phaseolus vulgaris L.): the biofortified carioca b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Besides anthocyanins content, antioxidant activity determined by the ABTS method is reduced by the cooking process. These results corroborate those of Silva et al 46 who reported that cooking beans reduced the antioxidant capacity compared to that of the grain in natura.…”
Section: Discussionsupporting
confidence: 92%
“…Besides anthocyanins content, antioxidant activity determined by the ABTS method is reduced by the cooking process. These results corroborate those of Silva et al 46 who reported that cooking beans reduced the antioxidant capacity compared to that of the grain in natura.…”
Section: Discussionsupporting
confidence: 92%
“…The cooking process was responsible for changes in the beans' accessible compounds. A reduction in the TPC (-61 %) was detected after cooking, and it was comparable to the TPC value described for the pinto cooked beans (40) , representing 63-77 % of the TPC determined in the raw seeds of pinto beans (41) . Most of the studies on beans are still focused on the TPC and only a few ones (41,42,(44)(45)(46)(47)(48)(49) on the individual phenolic compounds.…”
Section: Discussionsupporting
confidence: 80%
“…As far as we know, this work is the most complete study that has been performed to evaluate the bioavailability of phenolic compounds from cooked common beans, using UPLC-Q-TOF-MS. Based on the phenolic content of the three Portuguese studied varieties, the Portuguese common bean variety Moleiro was chosen as the variety with the highest TPC ( Table 1). Despite of the morphological differences in the seed colour, the TPC of Moleiro raw beans, 3•36 (SD 0•11) mg GAE/g of raw seed DW (2•91 (SD 0•09) mg GAE/g of raw seed fresh weight (FW)), characterised by light brown seeds, was within the range of values described by Heimler et al (43) for light green, white and yellow varieties (1•17-4•40 mg GAE/g of raw seed FW) and by Silva et al (40) for pinto varieties, characterised by cream coloured seeds with speckles ( Table 2).…”
Section: Discussionsupporting
confidence: 72%
“…These results may be attributed to the extraction of soaked coats and soaked cotyledons, performed separately after the soaking process. Such procedure allowed a higher extraction rate of the free phenolic compounds present in coats fraction, since cotyledons removal could eliminate some phenolic-protein interactions [47]. For this reason, despite the phenolic compounds’ loss into the soaking water, an overall comparison of common beans TPC in whole flour and in soaked beans (calculated as the sum of the TPC determined, separately, in both soaked fractions, coats and cotyledons) showed that at least 51% of the TPC determined in non-soaked seeds was preserved after soaking, which contradicts the high decrease, −73%, in the TPC of soaked beans reported by Faller & Fialho (2012) [48].…”
Section: Resultsmentioning
confidence: 99%